Cellular Diversity and Differential Subcellular Localization of the G-Protein Gαo Subunit in the Mouse Cerebellum - Roldán-Sastre, Alberto; Aguado, Carolina; Martín-Belmonte, Alejandro; Alfaro-Ruiz, Rocío; Moreno-Martínez, Ana Esther; Luján, Rafael (Frontiers in Neuroanatomy, 2021)
Heterotrimeric guanine nucleotide-binding proteins (G proteins) transduce signals from G protein-coupled receptors (GPCRs) to effector ion channels and enzymes. Gαo, a member of the pertussis toxin-sensitive Gi/o family, is widely expressed in the brain, although its role within a neuronal context remains largely unknown. Using immunohistochemical and quantitative immunoelectron microscopy techniques, we have investigated the expression, cellular and subcellular localisation of Gαo in the cerebellar cortex. Histoblot revealed that Gαo is expressed in many brain regions, including the cerebellum. At the cellular level, Gαo protein was distributed in Purkinje cells, basket cells, stellate cells, granule cells and Golgi cells. At the subcellular level, pre-embedding immunoelectron microscopy revealed mainly a postsynaptic localisation of Gαo along the extrasynaptic plasma membrane of Purkinje cell dendritic shafts and spines, and dendrites of basket, stellate and granule cells. To a lesser extent, immunolabeling for Gαo was localised in different types of axon terminals establishing excitatory synapses. Moreover, post-embedding immunoelectron microscopy revealed the synaptic localisation of Gαo on PSDs of glutamatergic synapses between Purkinje cell spines and parallel fibre terminals and its co-localisation with GABAB1 in the same spines. Quantitative analysis of Gαo immunoparticles revealed they preferentially localised on the cytoplasmic face of the plasma membrane. Furthermore, the analysis revealed a high concentration of Gαo around excitatory synapses on Purkinje cell dendritic spines, but a uniform distribution in granule cell dendrites. These molecular-anatomical findings suggest that Gαo is a major signal transducer of specific GPCRs in different neuronal populations in the cerebellum.